Effects of different tillage systems, nitrogen and irrigation on growth indicators and water productivity of wheat (Triticum aestivum) - Ziaeyan, Abdolhossein; Mousavi, Seyed Majid; Moradi, Abolfath; Karami, Alidad; Zaraeian, Gholamreza; Ziaeian, Mohammad (The Indian Journal of Agricultural Sciences, 2020)
During 2015-2017, by using the strip split-split plot design and three line-source sprinkler irrigation systems, effects of 0, 90, 135, and 180 kg N ha-1 as urea, 3395, 3850, 4240, and 4610 m3 water ha-1 in conventional, minimum, and no-tillage systems were investigated to determine effects of tillage systems on the wheat (Triticum aestivum L) nitrogen and water requirements. Results indicated that the grain yield, component yield and water use efficiency were statistically significant across the tillage systems. Conventional tillage had the higher yield and water use efficiency followed by minimum tillage and then no-tillage. The highest grain yield in the conventional tillage system was achieved by combined application of 4610 m3 water ha-1 and 180 kg N ha-1 and in minimum tillage and no-tillage systems were achieved by combined application of 4610 m3 water ha-1 and 135 kg N ha-1. In all tillage systems, combined application of 3850 m3 water and 135 kg N per hectare is recommendable for the highest water use efficiency.